Identities, Language, and Wayang Gung of South Kalimantan - Rezqan Farid; Muhammad Yunus (ENLIT, 2021)
Art products are media to show the identities of their makers as well as the identities of society members enjoying them. Cultural and communal traits of society where the arts created and appreciated are reflected through the arts. Wayang Gung is a classic art from South Kalimantan rarely performed nowadays. Wayang Gung depicts cultural values of Banjarese people in the past. As one of valuable oral literatures of Banjarese, linguistic element of Wayang Gung is worth investigating to reveal identities and cultural trace of Banjarese people. In this study, scripts of Wayang Gung are collected through documentation technique and analyzed using Ethnolinguistics approach. Ethnolinguistics is chosen for analyzing tool as it focuses on investigating language used in society with the culture of that society. Furthermore, ethnolinguistics seeks to reveal identities of the language users. The results of this study show that Banjarese people consider.